O uso do marketing pelo personal trainer e suas estrategias de mercado - MARQUES, Tiago Machado (2020)
The Personal Trainer unfolds to meet the demands of his career, such as: advertising, loyalty and investments. The purpose of this study is to understand the use of marketing strategies in the capture and retention of clients by Personal Trainers acting in a medium-sized gym in the city of Belém. As well as: a) defining how the Personal Trainer and customer relationship occurs within the context of strategies; b) identify the most cost-effective tools; c) to point out the current scenario about clarification about marketing. It is an exploratory research of qualitative analysis of the data obtained through the questionnaire containing 33 questions pertinent to the profile, service, pricing, strategies and knowledge about marketing. It was found that the Personal Trainers use strategies such as: a) diversification of the spaces in the accomplishment of the service, although most act in academies; b) carry out promotions for old students or when there is addition of students; c) use of database to add value and responsibility to the service; d) stimulates and participates with the student of sporting events. The dissemination of their service takes place more efficiently in social networks (Instagram and Facebook), where they present more satisfactory results in relation to the cost-benefit. It was recorded that a good portion of the sample says to have references about marketing, but this data does not want as far as good notions of marketing had by the Personal Trainers. We conclude that it is necessary to take more ownership of the use of marketing strategies by Personal Trainers to obtain more satisfactory results within the complexity of their performance.